2020
DOI: 10.1016/j.beproc.2019.104029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of hissing calls in five tit species

Abstract: Nest predation often leads to breeding failure, and is an important selective pressure of natural selection that affects nest defense behavior in birds. Many tit species give a hissing call for nest defense, but there are few studies on interspecific variation in hissing calls and whether these are related to nest predation and nesting success. In this study, we compared the hissing calls of five tit species including cinereous tit (Parus cinereus), marsh tit (Poecile palustris), varied tit (Sittiparus varius)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, hissing calls are not always successful enough to deter the predator away, because the efficiency of hissing calls relies on the fact that predators respond to hisses (Wickler, 2013 ). For example, the rate of nest predation of Japanese tits, willow tits ( Poecile montanus ), and coal tits ( Periparus ater ) that hissing and nonhissing is similar in Saihanba National Forest Park in China (Zhang et al, 2020 ). Similarly, we also found that the hissing calls of Japanese tit did not work for the jay in our observation.…”
Section: Discussionmentioning
confidence: 99%
“…However, hissing calls are not always successful enough to deter the predator away, because the efficiency of hissing calls relies on the fact that predators respond to hisses (Wickler, 2013 ). For example, the rate of nest predation of Japanese tits, willow tits ( Poecile montanus ), and coal tits ( Periparus ater ) that hissing and nonhissing is similar in Saihanba National Forest Park in China (Zhang et al, 2020 ). Similarly, we also found that the hissing calls of Japanese tit did not work for the jay in our observation.…”
Section: Discussionmentioning
confidence: 99%
“…This call has not previously been recorded in Marsh Tits, and perhaps only in Black-capped Chickadees among the parids (Clemmons 1995). The squawk call is similar to a very short version of the defensive 'hissing call', used by Marsh Tits and other tits to repel predators, consisting of a broad frequency 'white noise' sound (Zub et al 2017, Zhang et al 2020. A hiss-type call has also previously been reported from 15-day-old Marsh Tit nestlings in response to a perceived threat (Broughton 2005).…”
Section: Discussionmentioning
confidence: 81%
“…The expansion of digital sound recording in recent decades, and the availability of software to easily analyse and display it visually as sonograms (or spectrograms), has enabled a massive increase in the number and variety of sound recordings of birds, as can be found in online databases such as xeno-canto (www.xeno-canto.org). These developments have expanded the documented repertoire of the Marsh Tit since Cramp & Perrins (1993), to include fledgling begging calls (Broughton 2009) and the 'hissing' defensive call of incubating or brooding females within the nest (Zub et al 2017, Zhang et al 2020).…”
mentioning
confidence: 99%